2020
DOI: 10.35848/1347-4065/ab7c93
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of structural, electronic, and optical properties of ternary metal sulfides MBiS2 (M = Ag, Na)

Abstract: We study the structural, electronic, and optical properties of MBiS2 (M = Ag, Na) using the relativistic all-electron calculations. We find that for both M = Ag and Na, the and superstructures are the lowest-energy superstructures. and MBiS2 are indirect band-gap semiconductors with the differences between the indirect and direct band gaps, Δ, of about 0.5 and 0.1 eV for M = Ag and Na, respectively. and MBiS2 exhibit high absorption coefficients of the order of 105 cm−1. Employing the spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
(193 reference statements)
0
7
0
Order By: Relevance
“…AgBiS 2 photodetector has exhibited broadband response with decent detectivity, and fast response of 700 ns reported by L. Jiang et al, (2020) [14]. S. Suzuki et al, (2020) [15], L. Mehdaoui et al, (2019) [16], Y. Wu et al [17] and J. V. Embden et al, (2019) [3] have reported the optical absorption coe cient above 10 5 cm -1 for this material. M. Z.…”
Section: Introductionmentioning
confidence: 58%
“…AgBiS 2 photodetector has exhibited broadband response with decent detectivity, and fast response of 700 ns reported by L. Jiang et al, (2020) [14]. S. Suzuki et al, (2020) [15], L. Mehdaoui et al, (2019) [16], Y. Wu et al [17] and J. V. Embden et al, (2019) [3] have reported the optical absorption coe cient above 10 5 cm -1 for this material. M. Z.…”
Section: Introductionmentioning
confidence: 58%
“…We carried out all-electron calculations of the structural, electronic, and optical properties of MABiChI 2 and MAPbI 3 based on the DFT; 20,[36][37][38][39][40][41][42] the calculations of MAPbI 3 are for comparison to MABiChI 2 . The generalized gradient approximation (GGA) to the exchange-correlation energy functional was adopted using the Perdew-Burke-Ernzerhof (PBE) form.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…The absorption coefficients were obtained from the optical conductivity calculated within the independent particle approximation combined with a phenomenological approach. 20,[39][40][41][42] The optical transition matrix elements were also calculated using the four-component spinors to take into account all the relativistic effects including SOC. The phenomenological relaxation-time parameter ℏ/τ was used to simulate the lifetime of excitations; for all the materials studied in this work, ℏ/τ = 0.3 eV was used.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…In a series of AgBiE 2 , bulk AgBiS 2 possesses a bandgap of ≈1.2 eV, along with a high absorption coefficient of ≈10 5 cm −1 . [ 166,167 ] These two features allow AgBiS 2 for a potentially high‐efficiency PV device. In 2016, Bernechea et al.…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%
“…Map of compounds containing ns 2 cations with different structural dimensionalities (from 0D to 3D), involving the bandgaps and packing factors. The bandgap values include theoretical [ 16,69,86,101,129,130,135,137,143,144,166,175,178,181,225,226,289 ] and experimental [ 77,82,87,94,107,124,173,174,217,249,272,273,279,291 ] results, and the corresponding citation of the data source is marked at the top right.…”
Section: Conclusion and Perspectivementioning
confidence: 99%